Deutsche Bank AG : spying on stakeholders - Oji, Chijioke; Makin, Viola, 1952- ([London] : SAGE, 2016)
In May 2009, news of Deutsche Bank's spying operations became public. Over a period of six years, the bank's corporate security department had conducted secret surveillance of certain employees, board members and shareholders. Deutsche Bank had hoped to use the knowledge gained to its advantage in court or in the media. Thus, the bank faced the possibility of legal action instituted by the people it had spied on. This book examines the actions which had the potential to damage Deutsche Bank's reputation as a trustworthy institution.
Originally Published in: Oji, C., & Makin, V. (2013). Deutsche Bank AG: Spying on Stakeholders. WBS-2013-4. Johannesburg: The Case Centre, Wits Business School.
Description based on online resource; title from home page (viewed on April 27, 2016).
Keywords: elektronické knihy; electronic books; Deutsche Bank; Banks and banking -- Corrupt practices -- Case studies; Business intelligence -- Case studies; Business ethics -- Case studies